Perspectives of 3 T magnetic resonance imaging in radiosurgical treatment planning - Zamecnik, Patrik; Essig, Marco (Gamma knife neurosurgery in the management of intracranial disorders, 2013)
The introduction of 3 T magnetic resonance imaging (MRI) scanners for neuro-oncological diagnostics showed a general improvement of image quality, especially in terms of the detection and differentiation of intracranial tumors. Among the advantages of 3 T scanners compared to 1.5 T scanners are the possibility of higher spatial image resolution or shorter investigation times and the availability of functional imaging in sufficient quality. Consequently, the use of 3 T MRI for radiosurgery planning is highly desired. Functional MRI techniques (perfusion-weighted imaging, dynamic contrast-enhanced MRI, MR spectroscopy, diffusion-weighted imaging, and diffusion tensor imaging) available at 3 T scanners provide not only better detection and differentiation but also significantly better delineation of intracranial tumors, which is a crucial feature for successful radiosurgical treatment planning. The use of multimodal morphological and functional MRI methods allows identification of the biologically most active parts of the tumors with consecutive changes in therapy planning. On the other hand, there are increased geometric distortions on MRI scans obtained at 3 T compared to 1.5 T, which makes their use limited for now. However, the newest studies show an acceptable degree of geometric distortion on the 3 T planning images using special imaging protocols, while additional investigations on this issue are needed to find the optimal technical solution.